Evaluation of Investment Policies in Renewable Energies: The National Program for the Promotion of Renewable Energy and Energy Efficiency in Algeria 2011-2020 - Letaief, Walid (Finance and Business Economies Review, 2022)
This study aims to evaluate the effectiveness of the national program for the development of renewable energies as one of the other sectors of the economy in Algeria for the period 2011-2020. We used the descriptive method to analyze the extent to which the objectives of the program were achieved. The study concluded that the share of renewable energy, i.e. primary electricity, in the national energy mix did not exceed 0.1%, in addition to the delay in implementing the program's projects, and the failure to invest in all the targeted renewable energy sources.